Possible involvement of iron-induced oxidative insults in neurodegeneration. (19th February 2015) - Asano, Takeshi; Koike, Masato; Sakata, Shin-ichi; Takeda, Yukiko; Nakagawa, Tomoko; Hatano, Taku; Ohashi, Satoshi; Funayama, Manabu; Yoshimi, Kenji; Asanuma, Masato; Toyokuni, Shinya; Mochizuki, Hideki; et al.
Graphical abstract: Highlights: Increase of IRP2 accumulates iron that can provoke mitochondrial oxidative insults. Mitochondrial oxidative insults are induced in neurons in IRP2 transgenic (Tg) mice. Parkin appears involved in removal of iron-induced mitochondrial oxidative insults. IRP2 increase degenerates dopaminergic neurons synergistically with loss of Parkin. The IRP2 Tg mice may be useful to probe the roles of iron in neurodegeneration. Abstract: Involvement of iron in the development of neurodegenerative disorders has long been suggested, and iron that cannot be stored properly is suggested to induce iron toxicity. To enhance iron uptake and suppress iron storage in neurons, we generated transgenic (Tg) mice expressing iron regulatory protein 2 (IRP2), a major regulator of iron metabolism, in a neuron-specific manner. Although very subtle, IRP2 was expressed in all regions of brain examined. In the Tg mice, mitochondrial oxidative insults were observed including generation of 4-hydroxynonenal modified proteins, which appeared to be removed by a mitochondrial quality control protein Parkin. Inter-crossing of the Tg mice to Parkin knockout mice perturbed the integrity of neurons in the substantia nigra and provoked motor symptoms. These results suggest that a subtle, but chronic increase in IRP2 induces mitochondrial oxidative insults and accelerates neurodegeneration in a mouse model of Parkinson's disease. Thus, the IRP2 Tg may be a useful tool to probe the roles of iron-induced mitochondrial damages in neurodegeraration research.